PRELIMINARY PHYTOCHEMICAL SCREENING AND GAS CHROMATOGRAPHY AND MASS SPECTROMETRY ANALYSIS OF CHLOROFORM EXTRACT OF GARCINIA CAMBOGIA FRUITS - PRIYADHARISINI J, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Garcinia cambogia fruit commonly known as Malabar tamarind, belongs to the family Clusiaceae, is said to show varied medicinal effects including antiobesity, antiviral, antimicrobial, anti-inflammatory, and anticancer. Hence, the present study deals with the determination of phytochemical constituents present in the chloroform extract of G. cambogia fruits and determination of bioactive compounds using the gas chromatography and mass spectrometry analysis (GC-MS) technique. Methods: The phytochemical constituents present in the chloroform extract of G. cambogia fruits were tested by qualitative analysis, and bioactive compounds were investigated using the GC-MS technique. The analysis was carried out on a JOEL GC MATERI system with a column packed with a column HP5MS (5% phenyl, methylpolysiloxane) fused capillary column (30 × 0.25 μm ID × 0.25 μm df). The compounds are separated using helium as a carrier gas at a constant flow 1 ml/min. The mass spectra of the known compounds in the fruit extract were matched with the known components stored in the National Institute of Standard and technology library. Results: The phytochemical test revealed the presence of xanthones, flavonoids, phlobatannins, terpenoids steroids, phenolic compounds saponins, and anthraquinones. The GC-MS analysis provided peaks of 13 different bioactive compounds, namely 3,7,11,15-tetramethyl-2-hexadecenol (37.1%), pentadecanoic acid 14-methyl-, methylester (100%), hexadecanoic acid 15 methyl-, methyl ester (100%), 9,12-octadecadienoic acid methyl ester (42.6%), docosanoic acid (100%), docosanoic acid methyl ester (37.3%), phenol, 2,4,bis1,1-dimethylethyl) (100%), 9, hexadecanoic acid methyl ester (99.2%), 10-octadecenoic acid methylester (100%), 11 eicosenoic acid methyl ester (53.1%), heptadecanoic acid 9 methyl-, methyl ester (100%), eicosenoic acid methyl ester (56.9%), and 5, 12d ethanofuro oxepino[2,3,4-mn] (2,3,4-ed) anthrace2-one 9,12-dilol 6 methyl,2a 3,4,4a,5,6,7,8a‑octahydro (19%) were reported. Conclusion: The phytochemical investigation and determination of bioactive compounds will be considered for pharmacological activities, and further isolation of individual components would however help to find new drugs.